EVALUATION OF B1 GENE TO DETECT Toxoplasma gondii: COMPARISON OF THREE SETS NESTED PCR PRIMER - Ekawasti, Fitrine; Azmi, Zul; Subekti, Didik Tulus; desem, muhammad ibrahim; Nugraha, Arifin Budiman; Sadiah, Siti; Cahyaningsih, Umi (Universitas Syiah Kuala, 2023)
This study aimed to evaluate three sets of B1 gene DNA primer for the diagnosis of Toxoplasma gondii. The DNA of Toxoplasma gondii that stored on liquid nitrogen was isolated using DNAzol reagent. The first step of Polymerase Chain Reaction (PCRs) was performed using external and internal primer sets, respectively, and then nPCR. PCR products sequencing was performed by Apical Science. All sequences were analysed using CLC Sequence Viewer Version 8.0 software and compared to sequence database that deposited in ToxoDB (Toxoplasma gondii genome database) using BLAST (https://toxodb.org/toxo/app). Each B1 gene primer was evaluated by performing single PCR (forward and reverse) and nested PCR reactions. Three sets of B1 gene primer have different amplification precision. According to the results of amplicon sequencing, the primer set #2 has the best amplification precision of B1 gene.